The impact of leadership style, reward system, environmental strategy and environmental management accounting on environmental performance of Vietnamese manufacturers. - Vo Tan Liem (PLoS ONE)
The Upper Echelons Theory (UET) was employed in this study to examine the effects of Green Transformational Leadership (GTL) on the Green Reward System (GRS), Proactive Environmental Strategy (PES), Environmental Management Accounting (EMA), and Environmental Performance (EP). The data was collected from 198 CEOs of Vietnamese manufacturing enterprises by using a survey technique. The hypotheses were tested by using SmartPLS3, and the results indicate that all hypotheses are statistically significant. This research made a theoretical contribution to UET by investigating the key roles of GTL, GRS, PES, and EMA in the attainment of environmental performance. The study's results have suggested that top managers and organizational policymakers should implement the practices of the CEO's GTL, as well as GRS, PES, and EMA, to address stakeholders' environmental sustainability concerns and preserve their market position.